O sujeito em questão: a arqueo-genealogia das ciências humanas em Michel Foucault - Bays, Deise Gabriela (Universidade do Vale do Rio do Sinos, 2010)
For the French philosopher Michel Foucault, the emergence of man as subject is a recent event, resulting from a rearrangement of the space that regulates the production of knowledge, which occurred between the eighteenth and nineteenth centuries. This reconfiguration allowed the man was done simultaneously subject and object of knowledge with scientific pretensions. In fact, according to Foucault, until the classic modernity, the man did not question the very act of representing; did not think himself as subject of representation. Only when he was conceived by empirical knowledge related to his work, his language and his life, the man came to represent to himself his finite subjective condition. Thus, in Foucault’s perspective, the subject has no transcendental status or fixed essence. He is just a discursive figure - exposed, like others, to the determinations of language – whose emergence and conditions of existence only an archeo-genealogy, as a method of analysis focused in the discursive level, may discl
Keywords: ciências humanas; epistémê; genealogia; modernidade; sujeito; arqueologia; épistèmé; genealogy; human sciences; modern age; subject; archeology; Ciências Humanas